Foucault in sodobna literarna zgodovina - Širca, Alen Albin (Primerjalna književnost, 2010)
This paper problematizes the topicality of Foucault's thought in modern literary history. An analysis of the philosophical and historical implications of The Archeology of Knowledge makes it clear that his ideas do not involve the simple prioritizing of discontinuity over continuity called for by many contemporary literary historians and theoreticians, but a fundamental reflection on the (quasi)transcendental condition of both.
Keywords: Foucault, Michel, 1926-1984; književnost; literature; philosophy; filozofija; history of literature; literarna zgodovina; filozofija zgodovine; strukturalizem